The Impact of Pocket Money Management and QRIS Usage on Gen Z Consumptive Behavior: Evidence from Universitas Negeri Surabaya - Orlando Al Wahab Riskiyanto; Suci Rohayati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to analyze the partial and simultaneous effects of pocket money management and the use of QRIS digital payments on the consumptive behavior of Generation Z students in the Accounting Education Study Program, class of 2022, Universitas Negeri Surabaya. This research utilized a quantitative approach with an explanatory method. The sampling technique used was saturated sampling involving a total of 109 student respondents. Primary data were collected through the distribution of Likert-scale questionnaires. The collected data were then analyzed using classical assumption tests, hypothesis testing (t-test and F-test), and multiple linear regression analysis. The results proved that there is a negative and significant partial effect of pocket money management on consumptive behavior, indicated by a significance value of 0.000. Additionally, there is a negative and significant partial effect of using QRIS digital payments on consumptive behavior, which also showed a significance value of 0.000. The multiple linear regression analysis demonstrated that pocket money management and the use of QRIS digital payments simultaneously have a significant effect on student consumptive behavior. Furthermore, the adjusted R Square value indicates that these two independent variables can explain 20.1% of the variance in the students' consumptive behavior. The better the planning and management of pocket money, the lower the level of consumptive behavior among students. Furthermore, rather than increasing spending, the wise and monitored use of the QRIS system serves as an instrument of self-control capable of suppressing impulsive shopping habits.